When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia A.; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Losses Never Sleep - The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning

Lagerkapazitätsdimensionierung als betriebswirtschaftliches Entscheidungsproblem - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Strategische Erfolgsplanung für Produktinnovationen - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Tax Avoidance and Vertical Interlocks within Multinational Enterprises - Giese, Henning; Koch, Reinald; Gamm, Markus

Decision-making under Imperfect Information with Bayesian Learning or Heuristic Rules - Burs, Carina; Gries, Thomas
Information is one of the most important ingredients for decision-making. While the neoclassical assumption of perfect information is surely an important conceptual benchmark for discussing efficient allocations, it is obviously far from describing a rational choice under real conditions. In reality, optimal choices should be considered choices under imperfect information. Thus, decision-makers' information problem can be solved by two strategies. Either they collect an optimal set of information to make an optimal allocation choice under this imperfect information set or they can apply heuristic reasoning. In this paper, we suggest a formal model framework for the example of a simple consumer decision for the allocation of differentiated goods to explore information acquisition strategies in such a simple standard choice situation. Using the model variation under perfect information as a benchmark, we answer the following questions. First and most importantly, under imperfect information, can a heuristic rule substitute information acquisition as an optimal choice? Second, what is the role of risk aversion in the information acquisition process? Finally, we explore the differences to the benchmark, both ex ante the first purchase decision and ex post when repeated purchases and consumption allows for experiences with the choices made.
Keywords: information economics; imperfect information; Bayesian learning; risk; heuristics; differentiated products

The smoots Package in R for Semiparametric Modeling of Trend Stationary Time Series - Feng, Yuanhua; Gries, Thomas; Letmathe, Sebastian; Schulz, Dominik (The R Journal)
Keywords: Statistics; Probability and Uncertainty; Numerical Analysis; Statistics and Probability

Towards a Process Model for Social Media Marketing - Arslan, Kader; Trier, Matthias (Proceedings of the 33rd Australasian Conference on Information Systems (ACIS 2022))
Keywords: Social media; Social media marketing process; Social media strategy; Social media management; Guidelines

Möglichkeiten und Grenzen der Messung, Kontrolle und Sicherung der Qualität logistischer Prozesse - Hrnjadovic, Damir (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Implikationen einer wertorientierten Unternehmensführung für Standortplanungsentscheidungen - Fiedler, Moritz (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Betriebliche Standortplanung international agierender Unternehmen - Osthoff, Lennart (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Kategorisierungsmöglichkeiten für die Erzeugung von Dienstleistungen - Opitz, Oliver (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Entscheidungsunterstützung durch das Controlling mittels Reporting Design - Faupel, Christian (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Aktuelle Fragestellungen zu Produktion, Controlling und Logistik

Process Mining of Knowledge-Intensive Processes: An Action Design Research Study in Manufacturing - Löhr, Bernd; Brennig, Katharina; Bartelheimer, Christian; Beverungen, Daniel; Müller, Oliver (International Conference on Business Process Management)
Existing process mining methods are primarily designed for processes that have reached a high degree of digitalization and standardization. In contrast, the literature has only begun to discuss how process mining can be applied to knowledge-intensive processes—such as product innovation processes—that involve creative activities, require organizational flexibility, depend on single actors’ decision autonomy, and target process-external goals such as customer satisfaction. Due to these differences, existing Process Mining methods cannot be applied out-of-the-box to analyze knowledge-intensive processes. In this paper, we employ Action Design Research (ADR) to design and evaluate a process mining approach for knowledge-intensive processes. More specifically, we draw on the two processes of product innovation and engineer-to-order in manufacturing contexts. We collected data from 27 interviews and conducted 49 workshops to evaluate our IT artifact at different stages in the ADR process. From a theoretical perspective, we contribute five design principles and a conceptual artifact that prescribe how process mining ought to be designed for knowledge-intensive processes in manufacturing. From a managerial perspective, we demonstrate how enacting these principles enables their application in practice.

(How) do advanced data and analyses enable HR analytics success? A neo-configurational analysis - Strohmeier, Stefan; Collet, Julian; Kabst, Rüdiger (Baltic Journal of Management)
Purpose Enabled by increased (“big”) data stocks and advanced (“machine learning”) analyses, the concept of human resource analytics (HRA) is expected to systematically improve decisions in human resource management (HRM). Since so far empirical evidence on this is, however, lacking, the authors' study examines which combinations of data and analyses are employed and which combinations deliver on the promise of improved decision quality. Design/methodology/approach Theoretically, the paper employs a neo-configurational approach for founding and conceptualizing HRA. Methodically, based on a sample of German organizations, two varieties (crisp set and multi-value) of qualitative comparative analysis (QCA) are employed to identify combinations of data and analyses sufficient and necessary for HRA success. Findings The authors' study identifies existing configurations of data and analyses in HRM and uncovers which of these configurations cause improved decision quality. By evidencing that and which combinations of data and analyses conjuncturally cause decision quality, the authors' study provides a first confirmation of HRA success. Research limitations/implications Major limitations refer to the cross-sectional and national sample and the usage of subjective measures. Major implications are the suitability of neo-configurational approaches for future research on HRA, while deeper conceptualizing and researching both the characteristics and outcomes of HRA constitutes a core future task. Originality/value The authors' paper employs an innovative theoretical-methodical approach to explain and analyze conditions that conjuncturally cause decision quality therewith offering much needed empirical evidence on HRA success.
Keywords: Management of Technology and Innovation; Marketing; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management

The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Shortcut Learning in Financial Text Mining: Exposing the Overly Optimistic Performance Estimates of Text Classification Models under Distribution Shift - Caron, Matthew (2022 IEEE International Conference on Big Data (Big Data))
In recent years, many cases of deep neural networks failing dramatically when faced with adversarial or real-world examples have been reported. Such failures, which are quite hard to detect, are often related to a generalization problem known as shortcut learning. Yet, with state-of-the-art transformer models now being ubiquitous in financial text mining, one cannot help but wonder how reliable the results conveyed in the ever-growing literature genuinely are. Against this background, we expose, in this work, how vulnerable contemporary financial text mining approaches are to shortcut learning. Focussing on the common learning task of financial sentiment classification, we assess, using two entity-based sampling strategies and our publicly-available dataset, the discrepancies between i.i.d. and o.o.d. performance estimates of four transformer models. Our results reveal that o.o.d. performance estimates are consistently weaker than those of their i.i.d. counterparts, with the error rate increasing by as much as 29.7%, thus, demonstrating how this issue can, when overlooked, lead to misleading evaluations. Moreover, we show how additional preprocessing steps, such as entity removal and vocabulary filtering, can help reduce the effects of shortcut learning by filtering out entity-related linguistic cues.

Towards Automated Moderation: Enabling Toxic Language Detection with Transfer Learning and Attention-Based Models - Caron, Matthew; Bäumer, Frederik S.; Müller, Oliver (55th Hawaii International Conference on System Sciences (HICSS))
Our world is more connected than ever before. Sadly, however, this highly connected world has made it easier to bully, insult, and propagate hate speech on the cyberspace. Even though researchers and companies alike have started investigating this real-world problem, the question remains as to why users are increasingly being exposed to hate and discrimination online. In fact, the noticeable and persistent increase in harmful language on social media platforms indicates that the situation is, actually, only getting worse. Hence, in this work, we show that contemporary ML methods can help tackle this challenge in an accurate and cost-effective manner. Our experiments demonstrate that a universal approach combining transfer learning methods and state-of-the-art Transformer architectures can trigger the efficient development of toxic language detection models. Consequently, with this universal approach, we provide platform providers with a simplistic approach capable of enabling the automated moderation of user-generated content, and as a result, hope to contribute to making the web a safer place.

Commentaries on Relationship Marketing: The Present and Future of Customer Relationships in Services - Steinhoff, Lena; Palmatier, R. W.; Martin, K. D.; Fox, G.; Henderson, C. M.; Saint Clair, J. K.; Yan, S.; Lee, J.-Y.; Perko, T.; Harmeling, C. M. (Journal of Service Management Research)

Theorizing Marketplace Solidarity Systems: From Consumer–Firm Dyads to Structures of Mutual Support - Alberternst, B.; Steinhoff, Lena; Eggert, A.; Giesler, M. (2022 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)

How Do I Tell Them? Analyzing Companies' Provision of Rejection Reasons in Product Testing Programs - Garnefeld, I.; Steinhoff, Lena; Küpper, K. (2022 AMA Winter Marketing Educators’ Conference Proceedings, Las Vegas)

The Role of Self-Rewarding Behavior in Cashback Loyalty Programs - Becker, M.; Wiegand, N.; Steinhoff, Lena; Baidina, K. (Proceedings of the 51st European Marketing Academy (EMAC) Conference, Budapest.)

Transfer Pricing Rules for Intangibles: Implementation and Practical Challenges - Safaei, Reyhaneh

Changes in Transfer Pricing Regulations and Corporate Investment Decisions - Shabestari, Mehrzad Azmi; Safaei, Reyhaneh

Customer Engagement in International Markets - Steinhoff, Lena; Liu, J. (S.); Li, X.; Palmatier, R. W. (Journal of International Marketing)

Die Konstruktion von Geschäftsmodellen für nachhaltiges Wirtschaften: (k)eine exklusive Aufgabe des Managements?! - Schlömer, Tobias; Kiepe, Karina; Thrun, Tim (Intrapreneurship)

Steuerliche Maßnahmen als Anreiz für Investitionen? - Sureth-Sloane, Caren (Die Presse)

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der AG Nachwuchs im Verein für Socialpolitik - Bayer, Christian; Engelmaier, Florian; Riphahn, Regina T.; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg

Steuerpolitische Perspektiven der neuen Legislaturperiode - Chancen und Herausforderungen - Sureth-Sloane, Caren (FinanzRundschau)

Wissenschaften in der Coronavirus-Pandemie - Erkenntnisse, Wissens- und Handlungslücken sowie Schlussfolgerungen für die Vorbereitung auf künftige Pandemien - Interdisziplinäre Kommission für Pandemieforschung, DFG; Sureth-Sloane, Caren

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

E-Learning, Digitisation and Units for Learning at VET schools Creating Online Learning Environments in Technical Education for European metal industry. New Opportunities and Challenges for European VET schools in metal industry. Insights in the EDU VET Project

Family Business Library. Rural and Regional Libraries as Local family Entrepreneurship Centers. Policy Paper - Schneider, Jennifer Nicole

Wissenschaftliches Publizieren als Grundlage und Gestaltungsfeld der Wissenschaftsbewertung - Deutsche Forschungsgemeinschaft | AG Publikationswesen, (DFG); Sureth-Sloane, Caren
Academic publishing represents one of the core functions of scientific activity and thus of the research system. The Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) is committed to the adequate communication of research results and the maintenance of a functioning publication system as a basic requirement of the research system. Ensuring that academic publishing serves foremost the purposes of publicising, quality review and documenting scientific findings should be an essential goal of responsible science administration and promotion. The position paper therefore analyses the central background of the current situation in scientific publishing, identifies challenges and points out possible fields of action. With this positioning, the DFG contributes to the further development of the publication system in a way that is appropriate for science and research.

Curricular integration of academic and vocational education: a theory-based empirical typology of dual study programmes in Germany - Mordhorst, Lisa; Jenert, Tobias (Higher Education)
In Germany, dual learning programmes are increasingly offered by higher education institutions. These programmes’ main characteristic and greatest challenge is their integration of academic and vocational learning. So far, this challenge has frequently been stated without specifying its exact nature and consequences for learners. The present study addresses this pedagogical research gap and examines the extent of variation in the degree of integration among dual study programmes. With reference to curriculum theory, the study develops an empirical typology of curricular integration in dual programmes. The data sample consists of 152 programmes at (dual) universities and universities of applied sciences. Data is analysed using hierarchical cluster analysis. Results indicate that the currently prevailing forms of curricular integration should best be differentiated according to five types. The five overlapping types of integration are located on a continuum ranging from parallelism through organisational linking to full curricular integration targeted immediately at students’ personal integration. The analysis confirms that there are problems with complying with integration standards set on the policy level. Above all, the study offers new insights on what marks the diverse integration landscape of dual study programmes. It proves that approaches to integration are more differentiated than previous research has shown.
Keywords: Dual study programmes · Curricular integration · Curriculum theory · Empirical typology · Cluster analysis · Germany

Wissenschaftsdidaktik als Verständigung über wissenschaftliches Handeln – eine Auslegeordnung - Jenert, Tobias; Scharlau, Ingrid (Wissenschaftsdidaktik I: Einführung)
Im Zentrum Beitrags steht die Frage nach dem Spezifischen einer Didaktik im Wissenschafts- bzw. Hochschulkontext. Dabei hat die Organisation des Wissenschaftssystems in Disziplinen bzw. disziplinäre Gemeinschaften eine besondere Bedeutung. Disziplinen entwickeln spezifische Praktiken, die das Handeln ihrer Angehörigen prägen und sich in Fachkulturen zeigen. Diese Praktiken werden insbesondere an kommunikativen Artefakten sichtbar. Für Personen außerhalb einer disziplinären Gemeinschaft und ganz besonders für jene, die keinen direkten Bezug zum Wissenschaftssystem haben, sind disziplinäre Praktiken häufig schwer zu erschließen. Unsere Konzeption von Wissenschaftsdidaktik lenkt den Blick auf die impliziten Praktiken wissenschaftlicher Disziplinen. Aufgabe von Wissenschaftsdidaktik ist es dem- nach, erstens die impliziten disziplinären Sinnstrukturen, die hinter bestimmten Prak- tiken stehen und in kommunikativen Handlungen und Artefakten verschlüsselt sind, zu entschlüsseln. Zweitens ist es notwendig, die Wahrnehmung disziplinärer Praktiken durch die Studierenden zu analysieren und Differenzen zum Sinnverstehen von Wissenschaftler:innen zu identifizieren. Ausgehend davon kann dann drittens auf eine Verständigung über die Praktiken und deren Sinngehalt hingearbeitet werden. Der Beitrag formuliert die Grundzüge einer Wissenschaftsdidaktik, welche Verständigung über die Praktiken wissenschaftlicher Disziplinen zu einem Kernbestandteil akademischer Lehre macht. Dazu gehört auch ein Moment von Wissenschaftskritik, das auf die Disziplinen und deren Praktiken selbst zurückwirkt. Wissenschaftsdidaktik in diesem Sinne verlangt, den Blick Dritter auf die Praktiken der eigenen Disziplin einzunehmen. Dazu gehör auch, sich einzugestehen, wenn Praktiken keinen Sinn für wissenschaftliche Erkenntnisprozesse (mehr) aufweisen bzw. diesen verloren haben.
Keywords: Wissenschaftsdidaktik; Fachsozialisation; Wissenschaftskritik; Verständigung; Fachkultur; akademische Praktiken; Unterrichtsfach Psychologie

Digitale Transformation der Berufs- und Arbeitswelt – Einblicke in die fachdidaktische Gestaltung der beruflichen Fachrichtung ‚Wirtschaft und Verwaltung‘ - Jenert, Tobias; Kremer, H.-Hugo; Sänger, Niklas (bwp@ Berufs- und Wirtschaftspädagogik)
Die digitale Transformation führt dazu, dass sich lang etablierte Tätigkeiten und Arbeitsabläufe, welche die Berufsbilder im Kern definieren, verändern und stellt damit Mitarbeitende sowie Beteiligte der beruflichen Bildung vor Herausforderungen. Berufliche Lehramtsstudiengänge sind gefordert, Studierenden bereits im hochschulischen Teil ihrer Ausbildung den Aufbau eines berufsförmigen Wissens zu eröffnen, das ihnen die Erkundung beruflicher Handlungsfelder ermöglicht und eine wichtige Grundlage für die Unterrichtsgestaltung an Berufskollegs bildet. Wir geben in diesem Beitrag Einblicke in die Entwicklungsarbeiten einer fachdidaktisch geprägten Einführungsveranstaltung im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs. Diese zieht Ansätze der Fallstudiendidaktik heran, um für Studierende eine Möglichkeit zu schaffen, die digitale Transformation von Arbeits- und Geschäftsprozessen zu erkunden und diese mit Blick auf die Gestaltung von Wirtschaftsunterricht an Berufskollegs zu analysieren. Dabei stellen wir die Entstehung der Fallstudie sowie deren Einbettung in das Modulkonzept dar und diskutieren das hochschuldidaktische Lehr-/Lernformat.

Wissenschaftskommunikation als Verständigung: Chance für die Hochschulentwicklung?! - Jenert, Tobias; Scharlau, Ingrid (Zeitschrift für Hochschulentwicklung)

Mit dem SREL-Training unternehmerische Selbstkompetenzen entwickeln - Büker, Ronja; Jenert, Tobias; Fust, Alexander Paul; Fahrbach, Manuel; Bellwald, Noah; Winkler, Christoph (Erziehung & Unterricht)

Chance zur Reflexion - Scharlau, Ingrid; Jenert, Tobias (duz)

Entwicklung didaktischer Fallstudien zur Förderung einer ‚digitalen Inhaltskompetenz‘ im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung (An Empirical Analysis of Firms’ Hidden Cost of Taxation) - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren
Keywords: General Earth and Planetary Sciences; General Environmental Science

Towards an Amended Arm's Length Principle - Tackling complexity and implementing destination rules in transfer pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren

Firms' Tax Rate Misperception: Measurement, Drivers, and Distortionary Effects - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Sureth-Sloane, Caren

Chancen und Risiken eines Cooperative Compliance-Ansatzes für die deutsche Besteuerungspraxis von multinationalen Unternehmen – Erfahrungen verschiedener Länder und Eindrücke deutscher Unternehmensvertreter - Arbeitskreis Verrechnungspreise der Schmalenbach-Gesellschaft für Betriebswirtschaftslehre e.V., .; lead authors: Kreuzer, A; Maier, H; Martini, J. T.; Niemann, Rainer; Schachtebeck, Maite; Simons, Dirk; Stoltenberg, J; Sureth-Sloane, Caren (Internationales Steuerrecht)

A private sustainable partner selection model for green public-private partnerships and regional economic development - Tavana, Madjid; Khalili Nasr, Arash; Mina, Hassan; Michnik, Jerzy (Socio-Economic Planning Sciences)
Keywords: Management Science and Operations Research; Statistics; Probability and Uncertainty; Strategy and Management; Economics and Econometrics; Geography; Planning and Development

A multicriteria-optimization model for cultural heritage renovation projects and public-private partnerships in the hospitality industry - Tavana, Madjid; Azadmanesh, Abdolreza; Nasr, Arash Khalili; Mina, Hassan (Current Issues in Tourism)
Keywords: Tourism; Leisure and Hospitality Management; Geography; Planning and Development

A stochastic bi-objective simulation–optimization model for cascade disaster location-allocation-distribution problems - Khalili-Damghani, Kaveh; Tavana, Madjid; Ghasemi, Peiman (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A novel Interval Type-2 Fuzzy best-worst method and combined compromise solution for evaluating eco-friendly packaging alternatives - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A comprehensive framework for sustainable closed-loop supply chain network design - Tavana, Madjid; Kian, Hadi; Nasr, Arash Khalili; Govindan, Kannan; Mina, Hassan (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

A technology development framework for scenario planning and futures studies using causal modeling - Tavana, Madjid; Ghasrikhouzani, Mohsen; Abtahi, Amir-Reza (Technology Analysis & Strategic Management)
Keywords: Management Science and Operations Research; Strategy and Management

A multi-distance interval-valued neutrosophic approach for social failure detection in sustainable municipal waste management - Ebadi Torkayesh, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

An integrated rough group multicriteria decision-making model for the ex-ante prioritization of infrastructure projects: The Serbian Railways case - Pamucar, Dragan; Macura, Dragana; Tavana, Madjid; Božanić, Darko; Knežević, Nikola (Socio-Economic Planning Sciences)

A metaverse assessment model for sustainable transportation using ordinal priority approach and Aczel-Alsina norms - Pamucar, Dragan; Deveci, Muhammet; Gokasar, Ilgin; Tavana, Madjid; Köppen, Mario (Technological Forecasting and Social Change)

An efficient model-based branch-and-price algorithm for unrelated-parallel machine batching and scheduling problems - Shahvari, Omid; Logendran, Rasaratnam; Tavana, Madjid (Journal of Scheduling)

Analytics under uncertainty: a novel method for solving linear programming problems with trapezoidal fuzzy variables - Ebrahimnejad, Ali; Tavana, Madjid; Charles, Vincent (Soft Computing)

A socio-economic and environmental vulnerability assessment model with causal relationships in electric power supply chains - Vafadarnikjoo, Amin; Tavana, Madjid; Chalvatzis, Konstantinos; Botelho, Tiago (Socio-Economic Planning Sciences)

A new algorithm for modeling online search behavior and studying ranking reliability variations - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Applied Intelligence)

An information retrieval benchmarking model of satisficing and impatient users’ behavior in online search environments - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Expert Systems with Applications)

A dynamic location-arc routing optimization model for electric waste collection vehicles - Moazzeni, Sahar; Tavana, Madjid; Mostafayi Darmian, Sobhan (Journal of Cleaner Production)

An Integrated Data Mining Framework for Organizational Resilience Assessment and Quality Management Optimization in Trauma Centers - Tavana, Madjid; Nazari-Shirkouhi, Salman; Mashayekhi, Amir; Mousakhani, Saeed (Operations Research Forum)

An extended hybrid fuzzy multi-criteria decision model for sustainable and resilient supplier selection - Afrasiabi, Ahmadreza; Tavana, Madjid; Di Caprio, Debora (Environmental Science and Pollution Research)

Information acquisition and assimilation capacities as determinants of technological niche markets - Santos-Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora (Journal of Innovation & Knowledge)

A parameter tuned hybrid algorithm for solving flow shop scheduling problems with parallel assembly stages - Jabbari, Mona; Tavana, Madjid; Fattahi, Parviz; Daneshamooz, Fatemeh (Sustainable Operations and Computers)

A New Particle Swarm Optimization Algorithm for Optimizing Big Data Clustering - Hashemi, Seyed Emadedin; Tavana, Madjid; Bakhshi, Maryam (SN Computer Science)

A Review of Digital Transformation on Supply Chain Process Management Using Text Mining - Tavana, Madjid; Shaabani, Akram; Raeesi Vanani, Iman; Kumar Gangadhari, Rajan (Processes)

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric GARCH models with long memory are in- troduced. The estimation of the nonparametric scale function is carried out by an adapted version of the SEMIFAR algorithm (Beran et al., 2002). Recurring on the revised recommendations by the Basel Committee to measure market risk in the banks' trading books (Basel Committee on Banking Supervision, 2013), the semi- parametric GARCH models are applied to obtain rolling one-step ahead forecasts for the Value at Risk (VaR) and Expected Shortfall (ES) for market risk assets. In addition, standard regulatory traffic light tests (Basel Committee on Banking Supervision, 1996) and a newly introduced traffic light test for the ES are carried out for all models. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long memory GARCH models are an attractive alternative to their conventional, parametric counterparts.
Keywords: Semiparametric; long memory; GARCH models; forecasting; Value at Risk; Expected Shortfall; traffic light test; Basel Committee on Banking Supervision

Exogenous Shocks and Business Process Management - Röglinger, Maximilian; Plattfaut, Ralf; Borghoff, Vincent; Kerpedzhiev, Georgi; Becker, Jörg; Beverungen, Daniel; vom Brocke, Jan; Van Looy, Amy; del-Río-Ortega, Adela; Rinderle-Ma, Stefanie; Rosemann, Michael; Santoro, Flavia Maria; et al. (Business & Information Systems Engineering)
Abstract Business process management (BPM) drives corporate success through effective and efficient processes. In recent decades, knowledge has been accumulated regarding the identification, discovery, analysis, design, implementation, and monitoring of business processes. This includes methods and tools for tackling various kinds of process change such as continuous process improvement, process reengineering, process innovation, and process drift. However, exogenous shocks, which lead to unintentional and radical process change, have been neglected in BPM research although they severely affect an organization’s context, strategy, and business processes. This research note conceptualizes the interplay of exogenous shocks and BPM in terms of the effects that such shocks can have on organizations’ overall process performance over time. On this foundation, related challenges and opportunities for BPM via several rounds of idea generation and consolidation within a diverse team of BPM scholars are identified. The paper discusses findings in light of extant literature from BPM and related disciplines, as well as present avenues for future (BPM) research to invigorate the academic discourse on the topic.
Keywords: Information Systems; Business process management; Exogenous shocks; Challenges; Opportunities

From private digital platforms to public data spaces: implications for the digital transformation - Beverungen, Daniel; Hess, Thomas; Köster, Antonia; Lehrer, Christiane (Electronic Markets)
Technological developments such as Cloud Computing, the Internet of Things, Big Data and Artificial Intelligence continue to drive the digital transformation of business and society. With the advent of platform-based ecosystems and their potential to address complex challenges, there is a trend towards greater interconnectedness between different stakeholders to co-create services based on the provision and use of data. While previous research on digital transformation mainly focused on digital transformation within organizations, it is of growing importance to understand the implications for digital transformation on different layers (e.g., interorganizational cooperation and platform ecosystems). In particular, the conceptualization and implications of public data spaces and related ecosystems provide promising research opportunities. This special issue contains five papers on the topic of digital transformation and, with the editorial, further contributes by providing an initial conceptualization of public data spaces' potential to foster innovative progress and digital transformation from a management perspective.
Keywords: Digital transformation; Public data spaces; Digital platforms; GAIA-X

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Platform; Text mining; Machine learning; Data communications; Interpretive research; Systems design and implementation

Die Kommanditistenhaftung in der GmbH & Co. KG vor Registereintragung - Eine Untersuchung auf der Grundlage Digitaler Rechtstatsachenforschung - Bartlitz, David (Neue Zeitschrift für Gesellschaftsrecht (NZG))

Die Gesellschafterstruktur der GmbH & Co. KG aus der Perspektive der Digitalen Rechtstatsachenforschung - Bartlitz, David; Bohnert, Alexander (Zeitschrift für Wirtschaftsrecht (ZIP))

Die Begebung elektronischer Wertpapiere - Bartlitz, David (Neue Juristische Wochenschrift (NJW))

Leistungsverweigerungsrecht des Darlehensgebers aus §§ 358, 357 Abs. 4 Satz 1 BGB auch hinsichtlich vom Darlehensnehmer nach Widerruf erbrachter Leistungen. Anmerkung zu OLG Stuttgart, Urt. v. 22.03.2022 - 6 U 79/19 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Regulierung der Vergütungspraxis hochrangiger Mitarbeiter im Finanzdienstleistungssektor. Anmerkung zu EuGH, Urt. v. 01.08.2022 - C-352/20 - Bartlitz, David (Europäische Zeitschrift für Wirtschaftsrecht (EuZW))

Start-up-Gründung mit Schwierigkeiten - Bartlitz, David (Juristische Schulung (JuS))

§ 2 eWpG (Elektronisches Wertpapier) - Bartlitz, David (eWpG - Gesetz über elektronische Wertpapiere - mit weiterführenden Vorschriften - Kommentar)

Insolvcency Process in Germany and the insol database: A research Note - Ahlers, Theresa; Edossa, Fikir Worku; Uckert, Matthias; Kosi, Urska
This research note links the legal framework of the insolvency process of German firms to the information available in the newly-constructed insol database. In particular, the database contains information from documents published by German insolvency courts in period 2005- 2022. This research note first presents the insolvency process with steps and events of the process as determined by the Insolvency Law (InsO). Next, it classifies the documents to specific steps and events, and then presents their information content using textual analysis. Specifically, we identify target phrases via manual document checks and then create regular expressions for the target phrases. Classification of documents allows us to sketch most common paths that insolvent firms go through.
Keywords: insol database; insolvency process; Germany; court fillings

Current developments in the European corporate bond market - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
This paper introduces a novel database on the European corporate bond market to analyze the role of transparency regulation and recent developments in bond markets. We use data from the European Securities and Markets Authority (ESMA) to build a comprehensive database covering daily corporate bond listing information in Europe starting in 2018. We then analyze the different market segments of the European bond market along four key areas: (i) time and cross-sectional trends in bond listings; (ii) composition of firms on the market; (iii) firms’ financial reporting transparency; (iv) bond contract terms. Furthermore, we discuss the impact of recent economic events on these key areas.
Keywords: Transparency regulation; Corporate bond; European market

On Biases in Online Reviews and the Moderating Effect of Review System Design - Neumann, Jürgen

Inferring Quality with Reputation Systems - Experimental Evidence on Elicitation Mechanisms and Aggregation Metrics - van Straaten, Dirk

Studierende der Berufs-und Wirtschaftspädagogik: (Un-)bekannte Wesen? - Grunau, Janika; Jenert, Tobias (bwpat Spezial)

Dark triad managerial personality and financial reporting manipulation - Mutschmann, Martin; Hasso, Tim; Pelster, Matthias (Journal of Business Ethics)

Moment or Movement – An Empirical Analysis of the Heterogeneous Impact of Media Attention on Charitable Crowdfunding Campaigns - Müller, Michelle; Seutter, Janina; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Proceedings of the 42nd International Conference on Information Systems (ICIS))

"Timing is Everything" — An Empirical Analysis of the Timing of Online Review Elicitation - Poniatowski, Martin; Seutter, Janina; Kundisch, Dennis (Proceedings of the 42nd International Conference on Information Systems (ICIS))

Trust Me, I’m Confident – Are Confident Members of the Crowd Better at Evaluating Business Model Ideas? - Laux, Florian; Görzen, Thomas (Proceedings of the 42nd International Conference on Information Systems (ICIS))

The relationship between talent management and individual and organizational performance - Krebs, Benjamin; Wehner, Marius Claus (The Routledge companion to talent management)

Transitioning to Condition-Based Maintenance on the Distribution Grid: Deriving Design Principles from a Qualitative Study - zur Heiden, Philipp; Priefer, Jennifer (Pre-Conference 16th International Congress on Wirtschaftsinformatik at Universität Duisburg-Essen)

Option Implied Tax Rate Expectations - Eberbach, Jelena; Sureth-Sloane, Caren; Uhrig-Homburg, Marliese

Banks’ tax disclosure, financial secrecy, and tax haven heterogeneity - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren

Are Risk-based Tax Audit Strategies Rewarded? An Analysis of Corporate Tax Avoidance - Eberhartinger, Eva; Safaei, Reyhaneh; Sureth-Sloane, Caren; Wu, Yuchen

The Epidemiology of Tax Avoidance Narratives - Lorenz, Johannes; Diller, Markus; Sureth-Sloane, Caren
This study investigates the contagious nature of tax avoidance by examining how narratives affect tax avoiding behavior. We adapt the idea of narrative economics indicating that individuals' actions are stimulated by stories that spread within a society. We employ two types of infection models to theoretically investigate how tax avoidance schemes spread over time and vanish eventually consistent with patterns known from epidemiology. We find that general tax avoidance can persist even if its expected outcome is negative, while specific tax avoidance schemes might vanish even though their expected outcome is positive. We find empirical support for the predicted dissemination of narratives related to both general and specific tax avoidance schemes in google n-grams. Finally, we show that dissemination of specific tax avoidance schemes is attenuated by anti-narratives in (social) media. Our findings help to understand how tax avoidance spreads, under what conditions anti-avoidance measures can effectively curb tax avoidance and point towards the crucial role of transparency of enhanced enforcement by visible narratives.

A Comparison of Multi-View Learning Strategies for Satellite Image-based Real Estate Appraisal - Kucklick, Jan-Peter; Müller, Oliver (The AAAI-21 Workshop on Knowledge Discovery from Unstructured Data in Financial Services)

Drei Strategien zur Etablierung digitaler Plattformen in der Industrie - Lüttenberg, Hedda; Beverungen, Daniel; Poniatowski, Martin; Kundisch, Dennis; Wünderlich, Nancy (Wirtschaftsinformatik & Management)

Hybrid Intelligence in Hospitals: Towards a Research Agenda for Collaboration and Team-Building - Mirbabaie, Milad; Stieglitz, S.; Frick, N. (Electronic Markets)

The Development of Connective Action during Social Movements on Social Media - Mirbabaie, Milad; Brünker, F.; Wischnewski, M.; Meinert, J. (ACM Transactions on Social Computing)

Affording Technology in Crisis Situations: The Occurrence of Rumor Sense-Making Processes - Mirbabaie, Milad; Stieglitz, Stefan; Amojo, Ireti (Journal of Database Management)